The association between periodontal disease and adverse pregnancy outcomes: a bibliometric analysis from 2000 to 2023 - Zhao, Miaomiao; Chang, Haoxiang; Yue, Yuxu; Zeng, Xinyue; Wu, Shaobang; Ren, Xiuyun (Frontiers in Medicine, 2025)
BackgroundPeriodontal disease (PD) refers to a chronic inflammatory disorder affecting the supporting tissues of the teeth triggered by bacterial infection and is recognized to promote systemic inflammation, leading to dysfunction in specific organs. Adverse pregnancy outcomes (APOs), including preterm birth, small for gestational age infants, gestational diabetes and preeclampsia, are linked to pregnancy complications. Recently, the correlation between periodontal disease and adverse pregnancy outcomes has garnered global attention. However, bibliometric studies in this area remain limited. This study aimed to visualize knowledge framework and research trends concerning the relationship between periodontal disease and adverse pregnancy outcomes from 2000 to 2023 through bibliometric approaches.MethodsOn September 22, 2024, articles and reviews on the connection between periodontal disease and adverse pregnancy outcomes were retrieved from the Web of Science Core Collection (WOSCC). CiteSpace [6.3.R1 (64-bit) Advanced] was used to perform knowledge mapping and bibliometric studies.ResultsOver the past 23 years, 932 articles from 73 countries were collected, with the U.S. contributing over one-third (355), followed by Brazil (85) and India (59). The literature in this field has experienced multiple growth phases since 2000, with particularly rapid growth observed after 2019. The University of North Carolina (n = 34, 3.65%) is the leading institution in terms of publication output, primarily representing the U.S. Notably, the Journal of Periodontology and the American Journal of Obstetrics and Gynecology are the most frequently cited journals in the fields of periodontology and obstetrics, respectively. These publications are authored by 94 researchers, with Steven Offenbacher being both the most productive and most highly cited author, making significant contributions to the field. A visual analysis of keywords identifies “oral microbiota,” “oral health,” “adverse pregnancy outcomes,” and “global burden” as emerging research hotspots in exploring the correlation between periodontal disease and adverse pregnancy outcomes.ConclusionsThis first bibliometric and visual analysis of periodontal disease and adverse pregnancy outcomes offers a concise overview of the field and suggests future research should focus on risk factors, high-risk populations, oral microbiota, mechanisms, interventions, and international collaboration.